Adenomyoepithelioma of the breast with prominent cystic changes: a case report - Feng Chen; Hengping Wu; Yujian Liu; Minli Lv; Jianquan Zhong (BMC, 2021)
Abstract Background Adenomyoepithelioma (AME) of the breast is a rare subtype of breast tumor. Most of AMEs reported are solid, however, cystic or prominent cystic changes are extremely rare. Case presentation A 51-year-old woman presented a lump in the upper outer quadrant of right breast, and it was accompanied by continuous breast pain and bilateral axillary itching for more than 2 months. There were no other symptoms found. Preoperative mammography and ultrasound examination were performed. Mammography showed a noncalcified lobulated mass, and it was considered to be a benign cyst with septum on ultrasound, but ductal carcinoma of breast, adenoid cystic carcinoma could not be excluded. At first, AME was not considered preoperatively, because the imaging features of this rare tumor may vary widely, which may result in an incorrect diagnosis. But eventually, AME was diagnosed by postoperative pathology and immunohistochemistry. Conclusion We herein present a rare case of breast AME with prominent cystic changes. AME has no-specific imaging features, but the benign or malignant nature of the lesion might be suspected on imaging.